Ureteric injuries during cancer surgery presentation and management over a 20-year - Tohamy, Ali Zedan; Samy, Haisam A.; Salah, Tark; Hussien, Marwa T.; Hussein, Mohamed (International Surgery Journal, 2021)
Background: Iatrogenic ureteral injury rare 0.3-1.5%. complication of abdominopelvic cancer surgery. We aimed to study the risk and management of ureteral injury among cancer patients. Methods: Diagnosis can be achieved retrograde pyelography, ureteroscopy, CT, or intravenous urography. Results: Years 2000 to 2020, 2904 patients in the Department of Surgical oncology, Assuit University, and 47 ureteral injury cases were identified. (1.62), 4/231 cervical cancer, 9/611 ovarian cancer and 7/462 endometrial cancer.,11/818 colon cancer,12/620 rectal cancer, 1/11 prostatic cancer, 3/151 retroperitoneal sarcoma. 34% (radical abdominal hysterectomy 8.5% Wertheim hysterectomies 4%), colorectal surgery colectomy 25.5%, low anterior resection2.1% in radical prostatectomy and 6.4% in retroperitoneal tumor, intraoperative diagnosis 48.9%, 8.5% in laparoscopic surgeries, the distal third (53.2%),23.4% catheterization, complete transection 31.9%; partial 14.9%, ligation 8.5%, laceration in 19.1%, resection. 8.5%; and devascularization in 17%. Fever in 14.9%, abdominal or flank pain in 38.5%. Oligura in 6.4%, ileus in 19.3%, urinary leakage (vaginally or via abdominal wound) in 10.6% rise creatinine in 10.6%, hydronephrosis in 6.4%, urinoma in 27.7%, extravasation in 8.5% asymptomatic in 4.3%, 40.4% percutaneous nephrostomy. 19.1%primary repair Ureteroneocystostomy in (17%) Boari flap in 12.7%, Psoas hitch in 23.4% stenting in 14.9%, 8.5% ileum interposition, anastomosis to contralateral ureter in 4.3%, ureteral stricture 6.4%, ureterovaginal fistulas in 10.6%, acute renal failure 2.1%, peritonitis 4.3, urinary tract infection in 14.9%. Conclusions: The recognition and immediate repair of ureteral injuries early during the same procedure was highly desirable and to avoid a second operation.